2011
DOI: 10.1007/bf01616849
|View full text |Cite
|
Sign up to set email alerts
|

Use of thermotherapy in management of lymphedema: clinical observations

Abstract: We report clinical observations in 67 patients with chronic lymphedema undergoing hyperthermia. Our technique of hyperthermia is an alternative to microwave therapy, particularly where lymphangitis coexists in the same limb. Preoperative diagnostic evaluation including lymphatic and venous isotopic scintigraphy, Doppler venous flow metrics, and pressure manometry play an essential role in delineating the status of both the lymphatic and venous systems and in determining if hyperthermia is indicated. Our method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…After title and abstract screening, 78 full papers were retrieved, of which 18 studies were included (19 citations). Of these 19 included studies, 11 studies used a before-and-after design [ 18 , 19 , 29–37 ], four used a controlled before-and-after study design [ 38–41 ], three were randomised controlled trials (RCTs) [ 41–43 ], and one study used a cross-over randomized study design [ 44 ]. They were published between 1986 and 2022 [ 37 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After title and abstract screening, 78 full papers were retrieved, of which 18 studies were included (19 citations). Of these 19 included studies, 11 studies used a before-and-after design [ 18 , 19 , 29–37 ], four used a controlled before-and-after study design [ 38–41 ], three were randomised controlled trials (RCTs) [ 41–43 ], and one study used a cross-over randomized study design [ 44 ]. They were published between 1986 and 2022 [ 37 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…They were published between 1986 and 2022 [ 37 , 43 ]. These studies took place in various countries, of which seven were from China [ 30 , 32 , 34 , 36 , 37 , 40 , 41 ], four from Italy [ 19 , 29 , 31 , 38 ], three studies from Japan [ 35 , 42 , 45 ], two studies from India [ 18 , 39 ], and one study each from Brazil, Egypt, and USA [ 33 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Literature has suggested that increased skin temperature increases lymph flow rate and protein concentration, 29 however while thermotherapy has been suggested as an alternative management tool for lymphoedema, conflicting evidence exists around its true impact on lymph drainage. [30][31][32][33][34] This study aimed to explore the effects of a new compression garment (Tributewrap TM ) on tissue oxygenation and temperature in three different sitting positions in healthy adults. Due to the padded/quilted structure of this compression garment it is important to understand whether the chevron quilted structure of this compression garment leads to an increase in tissue oxygenation through its design, or through thermal therapy and a temperature increase.…”
Section: Introductionmentioning
confidence: 99%